RS and GIS-based assessment and modeling of urban environmental conditions for sustainable urban landscape development - Villanueva, Mylene J. (College of Engineering, University of the Philippines Diliman, 2015)
The concept of sustainable development is widely becoming an integral part of planning and decision making activities as the need to replace current resource-consuming and environmentally straining activities arises. In the context of spatial planning and urban development, sustainability focuses on the appropriate use and conservation of environmental components such as energy, greens, and natural areas, and the promotion of sound environment for the inhabitants. The outputs of spatial planning, however, cause direct and indirect environmental impacts which somehow contradict the criteria for sustainable urban development. This study addresses said concern through the assessment of the urban environmental conditions and development of a model which shall characterize the influence of urban environment attributes. Urban environmental conditions were described in terms of the thermal characteristics, vegetation distribution and urban built form. Spatial information and thermal profiles were extracted from remotely sensed data. LiDAR-derived elevation surface models were used to generate information on urban built form. These data together with other geographic datasets were stored in an urban geodatabase for use in subsequent spatial analyses. Urban thermal properties were correlated with vegetation densities, built-up distribution and surface reflectivity. The influence of urban built form on overall environmental condition was described using surface-to-volume ratio (SVR), sky view factor (SVF) and solar radiation. These variables were used in general linear regression and geographically weighted regression to develop the model for urban environmental condition. Surface temperature was considered as the dependent variable since it is a direct manifestation of the effects of a changing urban landscape. The explanatory variables include vegetation density, built-up distribution, surface albedo, SVR, SVF and solar radiation. Land use planning considerations were proposed based on the outputs of spatial analyses and modelling. The results of the assessment and model development provides for the identification of critical areas for improvement and preservation of urban environment; appropriate resources use and allocation; understanding of possible future scenarios; and formulation and carrying out of sound plans and informed decisions in relation to urban redevelopment. Ultimately, achieving the goals of this research contributes to the advancement of urban planning and development practices towards the fulfilment of sustainable urban development.